A preparative hydrophobic interaction chromatography for purification of recombinant nucleocapsid protein of Nipah virus from clarified Escherichia coli homogenate - Chong, Fui Chin; Tan, Wen Siang; Awang Biak, Dayang Radiah; Ling, Tau Chuan; Tey, Beng Ti (Elsevier, 2010)
The downstream processing of the recombinant nucleocapsid (N) protein of Nipah virus (NiV) from Escherichia coli homogenate using a preparative hydrophobic interaction chromatography (HIC) was investigated in the present study. Ammonium sulfate precipitation experiment was performed and it showed that 15% saturation of the salt was the most suitable salt concentration for the binding buffer. Batch binding of the N protein of NiV was performed using Sepharose™ 6 Fast Flow (FF) adsorbents coupling separately with four different types of ligand; phenyl low substitution, phenyl high substitution, butyl and octyl. The phenyl low substitution ligand was selected for subsequent optimization process due to its highest yield and purity of the N protein achieved from the batch binding experiment. The HIC for purification of the N protein of NiV was further scaled-up using a 10 cm column packed with phenyl low substitution Sepharose™ adsorbent. A recovering yield of 81% of the N protein of NiV with a purification factor of 9.3 was achieved from this scaled-up operation. The antigenicity of the purified N protein was still preserved as shown in ELISA analysis.